A WTO dairy ruling has possible implications for the EU sugar sector - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The WTO ruling on Canada's domestic support measures in the dairy sector,...